Evaluate the level of Oxidative Stress markers and Lipids Profile in Patients with Bening Prostate Hypertrophy in Al-Khadhmyah Tteaching Hospital - Fleih, aHanan H.; Al-Ani, aWajeeh Y.; Al- ma’adhedy, bSaddam h. (AL-Kindy College Medical Journal, 2014)
Background: Benign Prostate Hypertrophy(BPH)is a common urological problem worldwide which is defined as denomatous hyperplasia of the periurethralpart of prostate gland that occurs especially in men over 50 years old and that tend to obstruct urination by constriction the urethra Objectives: The study was aimed to investigate the level of Malondialdehyde (MDA), Nitric Oxide (NO) and Superoxide Dismutase (SOD) as an antioxidant, besides other factors such as the level of Lipids Profile (Total Chlosterol (TC), High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C), Very Low Density Lipoprotein Cholesterol (VLDL-C), and Triglyceride (TG))in patients suffer from BPH . Methods: In this study ;clinical ,specific prostate antigen and sonongraphy data of 80 persons were prospectively analyzed ; they are divided into two groups (40) male patients with Benign Prostate Hypertrophy (BPH) was previously diagnosed and another (40) healthy males as a control group .The study was performed at Al-Khadhmyah teaching hospital during the period from March 2001 till April 2003Results: The evaluated data recorded a significant increase in the levels of (MDA) and (NO), while a significant decrease in the level of (SOD) (P  0.001) in patients complain from BPH in comparison with the control group. Moreover, the results showed a significant increase in the levels of (TC), (TG) , (LDL-C) and a significant decrease in the level of (HDL-C) (P  0.001) in comparison with the control groupConclusions: Benign Prostate Hypertrophy (BPH) is the most common benign tumor in men and Malondialdehyde (MDA), Nitric Oxide (NO) ,Superoxide Dismutase and Lipid profile are beneficial markers to evaluate patients with BPH in comparison with those without BPH